Convert -36 Fahrenheit to Celsius

What is -36 degrees Fahrenheit in Celsius? Just type in either box, and the number in the other box will be converted automatically.
Fahrenheit
Celsius
-36° Fahrenheit = -37.78° Celsius
(rounded to 4 digits)
How hot is -36 degrees Fahrenheit? How cold? Convert between Fahrenheit and Celsius.
More temperatures starting with -36 degrees in Fahrenheit
Note: results are rounded
-36.00 °F = -37.78 °C -35.75 °F = -37.64 °C -35.50 °F = -37.50 °C -35.25 °F = -37.36 °C
-35.99 °F = -37.77 °C -35.74 °F = -37.63 °C -35.49 °F = -37.49 °C -35.24 °F = -37.36 °C
-35.98 °F = -37.77 °C -35.73 °F = -37.63 °C -35.48 °F = -37.49 °C -35.23 °F = -37.35 °C
-35.97 °F = -37.76 °C -35.72 °F = -37.62 °C -35.47 °F = -37.48 °C -35.22 °F = -37.34 °C
-35.96 °F = -37.76 °C -35.71 °F = -37.62 °C -35.46 °F = -37.48 °C -35.21 °F = -37.34 °C
-35.95 °F = -37.75 °C -35.70 °F = -37.61 °C -35.45 °F = -37.47 °C -35.20 °F = -37.33 °C
-35.94 °F = -37.74 °C -35.69 °F = -37.61 °C -35.44 °F = -37.47 °C -35.19 °F = -37.33 °C
-35.93 °F = -37.74 °C -35.68 °F = -37.60 °C -35.43 °F = -37.46 °C -35.18 °F = -37.32 °C
-35.92 °F = -37.73 °C -35.67 °F = -37.59 °C -35.42 °F = -37.46 °C -35.17 °F = -37.32 °C
-35.91 °F = -37.73 °C -35.66 °F = -37.59 °C -35.41 °F = -37.45 °C -35.16 °F = -37.31 °C
-35.90 °F = -37.72 °C -35.65 °F = -37.58 °C -35.40 °F = -37.44 °C -35.15 °F = -37.31 °C
-35.89 °F = -37.72 °C -35.64 °F = -37.58 °C -35.39 °F = -37.44 °C -35.14 °F = -37.30 °C
-35.88 °F = -37.71 °C -35.63 °F = -37.57 °C -35.38 °F = -37.43 °C -35.13 °F = -37.29 °C
-35.87 °F = -37.71 °C -35.62 °F = -37.57 °C -35.37 °F = -37.43 °C -35.12 °F = -37.29 °C
-35.86 °F = -37.70 °C -35.61 °F = -37.56 °C -35.36 °F = -37.42 °C -35.11 °F = -37.28 °C
-35.85 °F = -37.69 °C -35.60 °F = -37.56 °C -35.35 °F = -37.42 °C -35.10 °F = -37.28 °C
-35.84 °F = -37.69 °C -35.59 °F = -37.55 °C -35.34 °F = -37.41 °C -35.09 °F = -37.27 °C
-35.83 °F = -37.68 °C -35.58 °F = -37.54 °C -35.33 °F = -37.41 °C -35.08 °F = -37.27 °C
-35.82 °F = -37.68 °C -35.57 °F = -37.54 °C -35.32 °F = -37.40 °C -35.07 °F = -37.26 °C
-35.81 °F = -37.67 °C -35.56 °F = -37.53 °C -35.31 °F = -37.39 °C -35.06 °F = -37.26 °C
-35.80 °F = -37.67 °C -35.55 °F = -37.53 °C -35.30 °F = -37.39 °C -35.05 °F = -37.25 °C
-35.79 °F = -37.66 °C -35.54 °F = -37.52 °C -35.29 °F = -37.38 °C -35.04 °F = -37.24 °C
-35.78 °F = -37.66 °C -35.53 °F = -37.52 °C -35.28 °F = -37.38 °C -35.03 °F = -37.24 °C
-35.77 °F = -37.65 °C -35.52 °F = -37.51 °C -35.27 °F = -37.37 °C -35.02 °F = -37.23 °C
-35.76 °F = -37.64 °C -35.51 °F = -37.51 °C -35.26 °F = -37.37 °C -35.01 °F = -37.23 °C